A double-helical S, C-bridged tetraphenyl-para-phenylenediamine and its persistent radical cation. Issue 10 (12th January 2023) - Harada, Kaho; Hasegawa, Chika; Matsumoto, Taisuke; Sugishita, Hiroki; Kitamura, Chitoshi; Higashibayashi, Shuhei; Hasegawa, Masashi; Suzuki, Shuichi; Kato, Shin-ichiro
Abstract : The title compound has a sufficiently persistent radical cationic state and enough chiral stability for optical resolution. Abstract : A structurally constrained, double-helical S, C-bridged tetraphenyl- para -phenylenediamine (TPPD) has been synthesized. The stable radical cation of the S, C-bridged TPPD was generated by chemical oxidation, and the electron spin was found to be delocalized over the entire π-conjugated framework. The excellent conformational stability of the neutral molecule facilitated the separation of its enantiomers.